Construction project manager's perception on top job responsibilities in the context of Malaysia - Khan, Tareef Hayat (2015)
This paper presents an overview of Construction Project Manager's (CPM) responsibility in Malaysia. The construction sector plays a vital role in Malaysian economy and a very significant part of its' sustainable development. CPM is a professional who monitors all works in the construction project from top to bottom. The role of CPM is very important to identify their range of top responsibilities which might have different levels of priorities depending on the type of project.